Low Temperature EPR Spectra of the (Pr, RE)BaCuO Ceramics in the Orthorhombic Phase - Guskos, N.; V. Likodimos; Patapis, S.K.; Kuriata, J.; Wabia, M.; Sadlowski, L.; Koufoudakis, A.; Mitros, C.; Gamari‐Seale, H.; Psycharis, V (physica status solidi (b), 1994)
The EPR spectra of the members of the series Pr0.5RE0.5Ba2Cu3O6+x (RE = Pr, La, Nd, Sm, Eu, Gd, Dy, Ho, Y, Er, Tm, Yb, and Lu) in the orthorhombic phase are investigated at low temperature. The EPR spectra arise from two different paramagnetic centers, one from divalent copper ions in orthorhombic local crystal field symmetry and another from exchange coupled pairs of copper ions whose origin is discussed. The EPR spectra essentially depend on the time exposition. The EPR spectra of some divalent and trivalent rare earth ions are recorded. The crystal field analysis is done for the trivalent ytterbium ions. The semiconducting behaviour of the dc conductivity can be attributed to thermally activated small polaron hopping motion. Copyright © 1994 WILEY‐VCH Verlag GmbH & Co. KGaA
cited By 7